The Role of Personality as A Trigger For the Satisfaction of Valuable Bag - Retno Dewanti; Siti Nabila; Diana Simanjuntak; Siti Rohaida Mohamed Zainal (Social Economics and Ecology International Journal (SEEIJ), 2020)
Community empowerment activities through research results. This article is to investigated the influence of Hedonic Value and Utilitarian Value against Customer Satisfaction with moderating Personality has impacted to Behavioral Intentions on valuable bag. This research using Structural Equation Modeling (SEM) with Smart PLS 3.0 software. Data collected directly from respondents who meet the specified characteristics of population by distributing questionnaires. This study uses a sample of respondents who ever buy or use specific brand of bag. The samples used in this study were 100 respondents. The research findings indicate that hedonic and utilitarian values had a direct effect on customer satisfaction and have direct effect on behavioural intentions. In addition, customer satisfaction directly influenced behavioural intentions. The role of personality as the moderate variable in this study were able to amplify between customer satisfaction and perceived value.